Crossing Borders from France to Japan – and America (AmeriQuests, 2017)
Historical cross-cultural contact, between Japan and the West, and, in return, between the West and Japan, is a richly-textured and remarkably modern story. In this issue, we expand our understanding of material exchanges, and consider the introduction of French modernism to a reluctant space, far from the shores of France, or the US. And to put this issue into the current context, we can also consider the effects of building new walls, new restrictions, and new barriers to exchanges of all sorts, while also contemplating the “sanctuary” that can be offered in order to maintain our obligations, and to promote dignity rather than criminalization.